TRANSFORMASI PENDIDIKAN ISLAM DI ERA DIGITAL: TELAAH PEMIKIRAN YUSUF AL-QARADAWI - Yesshe Andes Balika (Jurnal Pendidikan Nusantara, 2024)
The development of digital technology has brought significant changes to the education system, including Islamic education. Yusuf al-Qaradawi, as one of the most prolific contemporary scholars, provides relevant insights on how Islam should respond to the changing times. This article examines the transformation of Islamic education in the digital age by referring to al-Qaradawi's ideas on the flexibility of Sharia law, the importance of ijtihad, and the urgency of utilising modern technology for da'wah and education. This study uses a qualitative approach through a literature review of al-Qaradawi's works, particularly those related to education and the use of technology. The results of the study show that Islamic education in the digital age must integrate the values of Sharia with technological innovation, strengthen spiritual competence as well as digital literacy, and develop a curriculum that is adaptive to the needs of the times.